2018
DOI: 10.1111/apha.13030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic hypoxia on diaphragm function in deer mice native to high altitude

Abstract: Overall, our work suggests that exposure to chronic hypoxia increases the capacities for mitochondrial respiration, force production and fatigue resistance of the diaphragm. However, many of these effects are opposed by evolved changes in diaphragm function in high-altitude natives, such that highlanders in chronic hypoxia maintain similar diaphragm function to lowlanders in sea level conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 58 publications
4
35
1
4
Order By: Relevance
“…It is interesting to note that our respiration values are lower than those reported by Braz-Mota et al 2018, although this is expected and has been shown in studies comparing different mitochondrial preparations in other taxa (Saks et al, 1998;Picard et al, 2011;Mahalingam et al, 2017). Mitochondrial respiration rates have classically been normalized using markers of mitochondrial volume, including CS and COX activity (Barrientos, 2002;Larsen et al, 2012;Dawson et al, 2018), and our mitochondrial respiration rates showed an excellent linear relationship (P=0.011, R 2 =0.689; Fig. 2B) with CS activity, suggesting that our measurements were the result of mitochondrion-based oxygen consumption.…”
Section: Resultssupporting
confidence: 45%
See 1 more Smart Citation
“…It is interesting to note that our respiration values are lower than those reported by Braz-Mota et al 2018, although this is expected and has been shown in studies comparing different mitochondrial preparations in other taxa (Saks et al, 1998;Picard et al, 2011;Mahalingam et al, 2017). Mitochondrial respiration rates have classically been normalized using markers of mitochondrial volume, including CS and COX activity (Barrientos, 2002;Larsen et al, 2012;Dawson et al, 2018), and our mitochondrial respiration rates showed an excellent linear relationship (P=0.011, R 2 =0.689; Fig. 2B) with CS activity, suggesting that our measurements were the result of mitochondrion-based oxygen consumption.…”
Section: Resultssupporting
confidence: 45%
“…The maximal activity (V max ) of citrate synthase (CS) and cytochrome c oxidase (COX) is commonly used as a measure of mitochondrial density (Larsen et al, 2012), so would be expected to correlate with measurements of mitochondrial respiration rate per unit mass of tissue. Activity was assayed at 12°C as previously described (Du et al, 2017;Dawson et al, 2018) using a SpectraMaxPlus 384 spectrophotometer (Molecular Devices, Sunnyvale, CA, USA). Samples were homogenized in 20 volumes of ice-cold homogenization buffer [in mmol l −1 : 100 KH 2 PO 4 , 1 EGTA, 1 EDTA and 1 phenylmethylsulfonyl fluoride (PMSF); pH 7.3].…”
Section: Gill Tissue Mitochondrial Enzyme Activitymentioning
confidence: 99%
“…This indicates that the bar-headed geese have evolved and adapted their muscle phenotype to sustain prolonged exercise in extreme hypoxia. Some recent studies have examined the changes in skeletal muscle phenotype that have occurred in high-altitude native deer mice (Lui et al, 2015 ; Scott et al, 2015 ; Mahalingam et al, 2017 ; Dawson et al, 2018 ). This rodent model is relevant to study this evolutionary adaptation because deer mice live within a range of altitude from below sea level to ~4,300 m above sea level.…”
Section: Adaptation Of Skeletal Muscle Fiber Type During Exposure Tomentioning
confidence: 99%
“…As it generally improves performance, it will probably also find broad acceptance as lifestyle drug for stressful episodes in life or as preconditioning drug for high altitude adaptation . How the effects of PHDis differ from real hypobaric hypoxia occurring at high altitude and how both conditions interact, are emerging but yet unexplored research fields . Via illegal markets, Roxadustat might also be taken in early pregnancy.…”
Section: Is There a Risk Of Roxadustat Abuse?mentioning
confidence: 99%
“…20,21 How the effects of PHDis differ from real hypobaric hypoxia occurring at high altitude and how both conditions interact, are emerging but yet unexplored research fields. 22,23 Via illegal markets, Roxadustat might also be taken in early pregnancy. If and how PHDis are affecting the development of the embryo or foetus is completely unknown.…”
Section: Roxadustat Abuse?mentioning
confidence: 99%